Parallel Tests of Whole Exome Sequencing and Copy Number Variant Sequencing Increase the Diagnosis Yields of Rare Pediatric Disorders - Hu, Xuyun; Guo, Ruolan; Guo, Jun; Qi, Zhan; Li, Wei; Hao, Chanjuan (Frontiers in Genetics, 2020)
Background: Both whole exome sequencing and copy number variants sequencing were applied to identify genetic cause of rare pediatric disorders. In our study, we aimed to investigate the diagnostic yield of parallel tests of trio whole exome sequencing and copy number variants sequencing and its clinical utility. Methods: After collecting detailed clinical information, a total of 60 patients were referred to parallel tests of whole exome sequencing and copy number variants sequencing which used shared initial libraries. Results: 26 pathogenic or likely pathogenic single nucleotide variants and 11 copy number variants were identified in 32 patients. 65.4% (17/26) of the SNVs were novel. The overall diagnosis rate was 53.3%. For the patients with positive results, 22 (36.7%) patients were diagnosed by whole exome sequencing and ten (16.7%) patients were diagnosed by copy number variants sequencing. We also reviewed clinical impact on selected cases. Conclusion: We adopted an approach by performing parallel tests of trio whole exome sequencing and copy number variants sequencing with shared initial libraries. This strategy is relatively efficient and cost-effective for the diagnosis of rare pediatric disorders with high heterogeneity.